Optimal Controller Design for Thermal Power System with Feedback Linearization - Ravi Shankar; Kalyan Chatterjee; T. K. Chatterjee (Institute of Advanced Engineering and Science, 2012)
The main objective of this paper is to device a method for construction of state-feedback control law for a single area thermal power system .In this method, first plant model is transformed into the controller form and constructs a state feedback controller in the new coordinates and then using the inverse transformation; represent the controller in the original coordinates. While constructing the controller in the new coordinates, a part of the controller is used to cancel nonlinearities, thus resulting in a linear system in the new coordinates. Simulation results in a single reheat thermal system are provided to illustrate the effectiveness of the proposed nonlinear control scheme.DOI:http://dx.doi.org/10.11591/ijece.v2i5.559